Quality Evaluation in Agile Process: A First Approach - Pinto, Noelia (2016)
In recent years, it has been given much importance to the use of models and quality standards on software development processes. Because these are those that facilitate continuous improvement and enable companies to provide higher quality products to its customers by increasing their competitive level. Today, software development is based on agile processes that allow production characterized by its changing requirements and the need for continuous customer deliveries environments. Thus it is imperative to provide companies with tools for assessing the quality of these cycles agile processes. QuAM is presented in this article, an approach to design a model of quality, integrated and flexible, that assesses the quality development cycles based on the principles and practices of the agile approach.